Methods for maximizing graduate students' learning experience: an insider's perspective - Hussin, Habsah (Australian International Academic Centre, 2014)
Graduate students furthering their studies at Master level are mature adult learners who bring with them a myriad of educational backgrounds and professional experiences into their studies. Delivering knowledge and information to them the traditional way via the lecture method per se may not be very effective anymore. They need methods that can utilize and make relevant their existing knowledge and professional experiences to help them realize their full potentials. This paper discusses the incorporation of four methods (individual presentation, dialogue, article critiquing and forum) into a graduate-level course (ESL Methodology) to supplement the lecture method, to provide variation in methods of teaching graduate students and as alternative measures for these graduate students to maximize their learning experience.